A New Method for Multi-hop Communication Over Bluetooth in Smartphones (International Journal of Engineering and Computer Science, 2018)
In this investigation, we built up a versatile application that gives scatternet organize setup utilizing Bluetooth interface on advanced mobile phones running Android Operating System to meet the communication needs of individuals,   where there is no Central Access Point, the Internet or physical framework on the earth. The messages transmitted on the system are transmitted shared in a multi-hop way. Each gadget that joins the system can act both server and shopper jobs. Every gadget likewise fills in as a switch. Companions partaking in the system can take in the current condition of the system from the gadget to which they are connected as a tree structure. Along these lines, each associate takes in the current structure of the system. In the meantime, a calculation was created and executed to spread the data of the recently included gadget to all reporters the system. The created application design is planned to be utilized as an elective specialized strategy in a wide range of outside and indoor situations, in regions where normal conditions, for example, mines are hard to impart, cataclysmic event territories, protect tasks, digital fear monger assaults and running remote sensor systems.